2004
DOI: 10.1007/s10198-004-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

Estimating rural households? willingness to pay for health insurance

Abstract: In many developing countries limited health budgets are a serious problem. Innovative ways to raise funds for the provision of health services, for example, through health care insurance, have a high priority. Health care insurance for rural households shields such patients from unexpected high costs of care. However, there are questions about whether, and how much, rural households are willing to pay to purchase such insurance, as well as the factors determining willingness to pay. In recent years the Iranian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(90 citation statements)
references
References 21 publications
9
77
4
Order By: Relevance
“…Some studies have shown that marital status influences the behavior of individuals towards health services 31 which also is in line with the finding from this study. The rural households (82.8%) were more willing to pay for community based health care financing than the urban households (61.6%), this was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Some studies have shown that marital status influences the behavior of individuals towards health services 31 which also is in line with the finding from this study. The rural households (82.8%) were more willing to pay for community based health care financing than the urban households (61.6%), this was found to be statistically significant.…”
Section: Discussionsupporting
confidence: 93%
“…25 Majority of urban household heads were civil servants (36.7%) while farming was the major occupation in the rural households (53.6%).Almost all the household heads were earning income monthly with mean income for urban heads to be ₦ 42± 5,200 and ₦10± 5,300 for rural heads as compared with a study in Enugu where majority of household heads were employed in Local Government jobs and others were into farming and the average household income was ₦10,141.20k per month for rural households. 19 The average household size was 4±2.2 for urban households and 5± 3.3 for rural households which is similar to result from a study in Ilorin North Central where household size average was 5.0± 2.7 31 and also the Nigeria demographic and health survey where the mean household size for urban households was 4.1 and 4.6 for rural households. 25 Only about half (52.0%) of the urban households were willing to pay for community based health care financing scheme as compared to the majority (83.0%) of rural households willing to pay for community based health care financing scheme.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Aged farmers may not see the need for long term sustainability of soil fertility and may be conservative to new ideas hence may show negative attitude towards the faecal sludge fertilizer. On the other hand, as they grow much older, they may become more experienced thereby willing to conserve the soil through the use of excreta pellets and hence positively influencing their WTP decision (Tessema & Holden 2006;Asgary et al, 2004;Dong et al, 2003).…”
Section: Determinants Of Willingness To Pay (Wtp) Amount For Excreta mentioning
confidence: 99%
“…Yet, there is an on-going debate on the relative advantages of different forms of health insurance (Asgary et al, 2004, Oxfam, 2008, ILO, 2008a. The purposes of health financing are to mobilise resources for the health system, to set the right financial incentives for providers, and to ensure that all individuals have access to effective health care.…”
Section: Models Of Health Insurancementioning
confidence: 99%